Salylic acid minimize cadmium accumulation in rice through regulating the fixation capacity of the cell wall to cadmium - Chen, Zhi Jian (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2023 Elsevier B.V. All rights reserved.